PENGARUH PERILAKU INOVATIF, MOTIVASI KERJA, DAN TEAMWORK TERHADAP KINERJA KARYAWAN YAYASAN LAUTAN CENDIKIA MULIA - Lulu Alviani; Audita Nuvriasari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of innovative behavior, work motivation, and teamwork on the performance of the Lautan Cendikia Mulia Foundation employees. This type of research is quantitive research and the data analysis method used is descriptive statistical analysis and inferential analysis. The research uses 38 respondents as research samples who are employees of the Lautan Cendikia Mulia Foundation. The results show that innovative behavior has a positive and significant effect on the performance of the Lautan Cendikia Mulia Foundation employees, while work motivation and teamwork have no significant effect on the performance of the Lautan Cendikia Mulia Foundation employees.